Antioxidant and Antibacterial Activities Enhancement of Solid-state Fermented Candlenut Kernels by Aspergillus oryzae - GRACE DOLOROSA LIMBONG; LEVY NATHANAEL NABABAN; ADELINA MANURUNG; MERRY MERYAM MARTGRITA (Indonesian Society for microbiology, 2019)
According to several studies, solid state fermentation (SSF) can enhance antioxidant and antibacterial activity of natural sources, and microorganism that is widely used in this kind of research is Aspergillusoryzae. Therefore, this study employed SSF by A. oryzae to enhance antioxidant and antibacterial activity of candlenut kernel. Candlenut kernel powder, that has been moistened with 60% water, was inoculated with 10% (w/w) of 5-day-culture ofA. oryzae, and was fermented for 9 days (until exponential phase; sample-1)and 12 days(until stationary phase; sample-2). The fermented candlenut kernels was extracted by ethanol and concentrated using rotary evaporator. Total phenolic content of control (unfermented extract), sample-1, and sample-2 are 0.183 mg GAE/g, 2.761 mg GAE/g, and 4.194 mg GAE/g, respectively. This results supported the IC50 value determined by DPPH method, those are 617.11 Î¼g/ml, 260.23 Î¼g/ml, and 45.29 Î¼g/ml. These results revealed a very strong antioxidant activity (< 50 Î¼g/ml) in the sample fermented until stationary phase.Antibacterial assay to Staphylococcus aureus resulted diameter of inhibition zone 7.17 mm, 13.51 mm, and 18.51 mm, respectively. And to Pseudomonas aeruginosa resulted diameter of inhibition zone 6.52 mm, 11.786 mm, and 15.269 mm, respectively. From this result, SSF until stationary phase enhanced higher antioxidant and antibacterial activity compared the other treatments.Â